2013
DOI: 10.1172/jci60681
|View full text |Cite
|
Sign up to set email alerts
|

WAVE1 mediates suppression of phagocytosis by phospholipid-derived DAMPs

Abstract: Clearance of invading pathogens is essential to preventing overwhelming inflammation and sepsis that are symptomatic of bacterial peritonitis. Macrophages participate in this innate immune response by engulfing and digesting pathogens, a process called phagocytosis. Oxidized phospholipids (OxPL) are dangerassociated molecular patterns (DAMPs) generated in response to infection that can prevent the phagocytic clearance of bacteria. We investigated the mechanism underlying OxPL action in macrophages. Exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The patient contained lipid-laden macrophages in the BAL, which the authors attributed to inhalation of glycerol-based E-cig vapor. Lipid-laden macrophages exhibit impaired bacterial phagocytosis [ 15 , 42 ]. Thus, it is likely that even E-cigs containing 0% nicotine will still alter the pulmonary response.…”
Section: Discussionmentioning
confidence: 99%
“…The patient contained lipid-laden macrophages in the BAL, which the authors attributed to inhalation of glycerol-based E-cig vapor. Lipid-laden macrophages exhibit impaired bacterial phagocytosis [ 15 , 42 ]. Thus, it is likely that even E-cigs containing 0% nicotine will still alter the pulmonary response.…”
Section: Discussionmentioning
confidence: 99%
“…The Tabas group showed that OxPL induce apoptosis in macrophages undergoing ER-stress via CD36/TLR2 activation[68] and Gerhard Kronke’s group reported that 12/15 lipoxygenase plays a major and unexpected role in the non-inflammatory clearance of apoptotic cells, via a mechanism involving the formation of oxidized phosphatidylethanolamines (OxPE)[20]. On the other hand, phagocytosis was shown to be inhibited in macrophages by mm-LDL[69] and OxPAPC[58], and Sylvia Knapp’s group discovered that this inhibition involves WAVE1[70, 71], which is a cytoskeleton bound A-kinase anchoring protein. The group showed that WAVE1 knockout macrophages are resistant to OxPAPC-inhibited phagocytosis, and that the E. coli infected chimeric WAVE1-knockout mice have a better survival rate compared to controls[71].…”
Section: Oxpl and Macrophages: Identification Of Moxmentioning
confidence: 99%
“…On the other hand, phagocytosis was shown to be inhibited in macrophages by mm-LDL[69] and OxPAPC[58], and Sylvia Knapp’s group discovered that this inhibition involves WAVE1[70, 71], which is a cytoskeleton bound A-kinase anchoring protein. The group showed that WAVE1 knockout macrophages are resistant to OxPAPC-inhibited phagocytosis, and that the E. coli infected chimeric WAVE1-knockout mice have a better survival rate compared to controls[71]. Altogether, this has important implications in the regulation and outcome of inflammatory responses in atherosclerosis and sepsis.…”
Section: Oxpl and Macrophages: Identification Of Moxmentioning
confidence: 99%
“…Oxidized phospholipids are CD36 ligands that promote inflammation via TLR2 activation in ischemic brain ( Cho et al, 2005 ; Abe et al, 2010 ). The recognition and endocytosis of oxidized lipids by pattern recognition receptors could regulate post-ischemic inflammation ( Miller et al, 2011 ; Matt et al, 2013 ).…”
Section: Inflammatory Dampsmentioning
confidence: 99%